On the development of working land management projects for the reclamation of disturbed lands - Koshel, A.; Kolhanova, I. (Land Management, Cadastre and Land Monitoring, 2023)
Scientific and methodical approaches to the development of working land management projects for the reclamation of lands disturbed by industrial production are proposed.After the completion of mining operations, their restoration, i.e. reclamation, must be carried out on the disturbed territories. Land reclamation is a complex of works aimed at restoring the productivity and economic value of disturbed lands, as well as improving environmental conditions in accordance with the interests of society.Any construction, mining, geological exploration, etc. cannot begin until a reclamation project for the disturbed soil cover is developed. Reclamation is subject to all lands undergoing changes in relief, soil cover, parent and underlying rocks that occur or have already occurred in the process of mining, construction, hydraulic engineering, geological exploration and other works.
Keywords: reclamation; working project of land management; disturbed lands; grounding; soil protection.